Pressure drop of different flow pattern in multiphase flow system - Mohammad Hafizezazmi, Ajamain (2015)
Multiphase flow is not an old issue to be discussed. Pressure drop and heat transfer under multiphase flow are very complicated to predict. Lots of empirical correlations have been made to predict pressure drop in pipelines under multiphase condition. Example of correlation used to predict pressure drop is Petalas-Aziz correlation, Begss-Brill correlation and Flannigan correlation. Under multiphase condition, different types of flow pattern can happen. In predicting pressure drop flow pattern is considered because different flow pattern will give a different pressure drop. In this study flow pattern is consider to determine the flow pattern. Flow pattern used is intermittent, stratified, annular and bubble flow. After determining the flow pattern, three empirical correlations used to predict the pressure drop which is Petalas-Aziz correlation, Beggs and Brill correlation and Flannigan correlation. Thus, to determine the flow pattern and pressure drop mathematical programming software is used which is FORTRAN. Using the programming code, predicting the pressure drop and determining flow pattern user can use it to design a better pipeline to encounter pressure loss.